The epidemiology of child homicides in South Africa - Shanaaz Mathews; Naeemah Abrahams; Rachel Jewkes; Lorna J Martin; Carl Lombard
Abstract Objective To describe age- and sex-specific rates of child homicide in South Africa. Methods A cross-sectional mortuary-based study was conducted in a national sample of 38 medicolegal laboratories operating in 2009. These were sampled in inverse proportion to the number that were operational in each of three strata defined by autopsy volume: < 500, 500-1499 or > 1499 annual autopsies. Child homicide data were collected from mortuary files, autopsy reports and police interviews. Cause of death, evidence of abuse and neglect or of sexual assault, perpetrator characteristics and circumstances surrounding the death were investigated. Findings An estimated 1018 (95% confidence interval, CI: 843-1187) child homicides occurred in 2009, for a rate of 5.5 (95% CI: 4.6-6.4) homicides per 100 000 children younger than 18 years. The homicide rate was much higher in boys (6.9 per 100 000; 95% CI: 5.6-8.3) than in girls (3.9 per 100 000; 95% CI: 3.2-4.7). Child abuse and neglect had preceded nearly half (44.5%) of all homicides, but three times more often among girls than among boys. In children aged 15 to 17 years, the homicide rate among boys (21.7 per 100 000; 95% CI: 14.2-29.2) was nearly five times higher than the homicide rate among girls (4.6 per 100 000; 95% CI: 2.4-6.8). Conclusion South Africa's child homicide rate is more than twice the global estimate. Since a background of child abuse and neglect is common, improvement of parenting skills should be part of primary prevention efforts.